PENGARUH STRUKTUR MODAL, EKONOMI MAKRO DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Susanti, Yessy; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to test the influence of capital structure, macro economy and profitability to the firm value of manufacturing companies which are listed in Indonesia Stock Exchange. The samples have been obtained by using purposive sampling method on manufacturing companies which are listed Indonesia Stock Exchange (IDX) in 2012-2015 periods and based on the predetermined criteria 131 manufacturing companies have been selected as samples. The analysis method has been done by using PLS (Partial Least Square) which is the alternative method of SEM (Structural Equation Model) and the application of Smart PLS 2.0. The result of the research shows that capital structure and macro economy does not have any influence to the firm value whereas profitability give positive influence to the firm value. The result of the research does not support the trade-off theory which states that when loan level is getting high, the firm value is getting high as well, but the result of this research support the signaling theory that every negative signal or positive from the company can give influence to every decision which has been made the investorsKeywords: capital structure, macro economy, profitability, firm value